Electrochemical sensitivity, selectivity, and sensory properties of a natural polymer-supported titanium nanocomposite electrode towards lysine amino acid - Altuner, Elif Esra (My University, 2023)
In this study, chitosan (Chit) supported titanium (Ti) nanoparticles (Ti@Chit NPs) were synthesized by chemical method. Ti@Chit NPs were calculated to be 7.275 ± 2.15 nm and 18.629 nm according to scanning electron microscopy (SEM) and atomic force microscopy (AFM) results, respectively. The synthesized NPs were modified to the electrode and a sensitivity study was carried out against lysine amino acid. It has been determined that the Ti@Chit electrode has a catalytic performance against the amino acid lysine. The limit of detection (LOD) value is estimated to average 0.0041 µM.
Keywords: Sensor; Lysine; Ti@Chit NPs